Digital Transformation for Sustainable Rural Tourism: Evaluating Branding Competencies in Taro and Keliki Tourism Villages - Putu Ade Wijana; I Putu Andre Adi Putra Pratama; I Gusti Ngurah Oka Widjaya; Isvari Ayu Pitanatri (Yayasan Ghalih Pelopor Pendidikan, 2026)
Digital transformation has become a key strategy for advancing sustainable rural tourism, yet many destinations struggle to translate digital access into effective branding outcomes. This study examines how digital branding competencies shape sustainable tourism development in two tourism villages in Gianyar, Bali, namely Taro and Keliki. Using a qualitative comparative case study approach, data were collected through in depth interviews with eighteen local stakeholders, participant observation, and a systematic audit of digital platforms. The analysis reveals that differences in digital performance are not primarily driven by technology availability but by variations in governance, human capital, and narrative coordination. Taro demonstrates an integrated digital branding model supported by institutional collaboration and clear role distribution, while Keliki exhibits fragmented practices reliant on individual initiatives. The findings highlight that sustainable digital transformation in rural tourism depends on institutionalized branding competencies rather than technical adoption alone